The Effect of Adding Ruku-Ruku Plant Essential Oil (Ocimumm tenuiflorum L.) as a Source of Antioxidants in Lip Balm Preparations - Diana Sylvi; Tuty Anggraini; Anggun Anggun (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
This study aims to evaluate the effect of adding ruku-ruku (Ocimum tenuiflorum) essential oil on the characteristics and antioxidant activity of lip balm, as well as to determine the best formulation. The research employed a Completely Randomized Design (CRD) with five treatments and three replications. The treatments consisted of different concentrations of essential oil: A (0%), B (1%), C (2%), D (3%), and E (4%). Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s New Multiple Range Test (DMRT) at a 5% significance level. Evaluated parameters included homogeneity, applicability, irritation test, and organoleptic properties (color, aroma, and texture). The results showed that treatment B (1% essential oil) was the best formulation, with a pH value of 5.61, homogeneous texture without coarse particles, uniform and colorless application, and no irritation. It exhibited antioxidant activity of 53.83% and increased moisture by 21.56%. Organoleptic scores indicated good panelist preference for color (4.04), aroma (3.52), and texture (4.16). The main compounds identified were eugenol, limonene, and caryophyllene. Further studies are needed to assess shelf life stability.